2008
DOI: 10.1063/1.2948905
|View full text |Cite
|
Sign up to set email alerts
|

ZnO quasibicrystals formed by thermal annealing

Abstract: Atmospheric annealing could melt the nanorods with diameters of ϳ10 nm at ϳ600°C, and completely change them into jointed grains at 610°C. Most of the jointed grains are quasibicrystals with nearly symmetric morphologies but twinning free structures, much different from the commonly observed ZnO twinning crystals. The quasibicrystals would also be formed when annealing ZnO nanoparticles, which may be a common thermal behavior of ZnO low dimensional nanostructures and should be considered when preparing ZnO nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Although the changes seen during annealing are instructive in terms of understanding the origin of effects seen during VPT growth, we do note, in relation to sublimation processes, that during the VPT process, the higher vapor pressure coming from the source limits the sublimation yield, and as a result this may restrict the morphological changes on the original CBD nanorod compared to the annealing process. To compound the complexity of the structural transformations observed, it has been reported that ZnO nanostructures can have melting temperatures well below that of the bulk material. At present, this phenomenon is poorly understood. Using the theoretical model put forward by Guisbiers et al, using the maximum and minimum differences between the surface tensions in the liquid and solid phases ((γ l – γ s ) = max/min value) yields a predicted melting temperature range of 1764–1883 °C for hexagonal nanorods with a 20 nm side length and height of 300 nm, well above the temperatures reached during our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Although the changes seen during annealing are instructive in terms of understanding the origin of effects seen during VPT growth, we do note, in relation to sublimation processes, that during the VPT process, the higher vapor pressure coming from the source limits the sublimation yield, and as a result this may restrict the morphological changes on the original CBD nanorod compared to the annealing process. To compound the complexity of the structural transformations observed, it has been reported that ZnO nanostructures can have melting temperatures well below that of the bulk material. At present, this phenomenon is poorly understood. Using the theoretical model put forward by Guisbiers et al, using the maximum and minimum differences between the surface tensions in the liquid and solid phases ((γ l – γ s ) = max/min value) yields a predicted melting temperature range of 1764–1883 °C for hexagonal nanorods with a 20 nm side length and height of 300 nm, well above the temperatures reached during our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…[1−3] Generally, materials of reduced size demonstrate melting points lower than those of their bulk forms. Because the melting point of bulk ZnO is as high as 1750 ∘ C, ZnO shows good thermal stability, [4−7] and the growth temperature for single crystalline ZnO thin films reaches 700-900 ∘ C. By the physical vapor transport method, one-dimensional (1D) ZnO nanostructures could be obtained with a growth temperature above 900 ∘ C. [8] However, some researchers recently reported that the melting point of ZnO nanorods grown by thermal decomposition or the hydrothermal method could be decreased to 600-700 ∘ C. [4] The diameters of these nanorods can be 10 nm to several tens of nanometers, and a morphological change in the ZnO nanostructures annealed at high temperature was reported, which was ascribed to the melting point decrease for the nano-sized ZnO. [9] Some theoretical works have also shown that the size and shape of ZnO nanostructures can affect the melting temperature 𝑇 𝑚 .…”
mentioning
confidence: 99%
“…A sensitivity of 19 for 4000 ppm CO at 300 ℃ has been observed for sensors based on SnO 2 PNSs [12], and Pt-loaded SnO 2 PNSs were even found to show obvious responses to CO at room temperature [13], although their response and recovery time are still needed to be shortened. As a matter of fact, with very large specific surface areas and high surface free energies, nanoparticles in contact can become connected to one another at contact points at relatively low temperatures [14], which is usually known as premature sintering, primarily in the case of sintering materials having a nanostructure, and leads to the formation of a highly porous microstructure with obviously enhanced mechanical strength. Presently, we have taken advantage of premature sintering to prepare several kinds of TiO 2 porous nanoceramics.…”
Section: Introductionmentioning
confidence: 99%